Flavonoids and other bioactive constituents from Ficus thonningii Blume (Moraceae). (March 2015) - Fongang, Yannick S.F.; Bankeu, Jean J.K.; Ali, Muhammad S.; Awantu, Angelbert F.; Zeeshan, Ahmed; Assob, Clement N.; Mehreen, Lateef; Lenta, Bruno N.; Ngouela, Silvere A.; Tsamo, Etienne
Graphical abstract: Highlights: Two new flavonoids and 19 known isolates from Ficus thonningii Blume (Moraceae). β -Isoluteone was isolated for the first time from a natural source. Extracts and isolates shown strong antioxidant and moderate antimicrobial testing. Abstract: Continued interest in the chemistry of Ficus spp. led to the investigation of the figs and the roots of Ficus thonningii Blume. Two new flavonoids, thonningiol (1 ) and thonningiisoflavone (2 ) along with nineteen known compounds were isolated. β -Isoluteone (13 ) was isolated here for the first time from a natural source. Their structures were elucidated on the basis of spectroscopic evidence. Interestingly, thonningiisoflavone (2 ) and hydroxyalpinumisoflavone (21 ) showed strong DPPH radical scavenging activity with IC50 = 65.50 μM and 68.20 μM respectively compared to the standard BHA with IC50 = 44.20 μM. The methanolic extract of figs, taxifolin (14 ), conrauiflavonol (17 ) and shuterin (19 ) exhibited moderate antimicrobial activity against six micro-organisms with MIC below 1.5 mg/mL.